MULTISCALE, MULTIMEDIA AND MULTIELEMENTAR GEOCHEMICAL MAPPING OF THE STATE OF PARANÁ, BRAZIL - Licht, Otavio Boni (Geochimica Brasiliensis, 2018)
The State of Paraná was the first Brazilian state to perform systematic geochemical surveys on a regional scale, complemented by some more detailed ones, focusing the town of Umuarama and its capital Curitiba as well. In these surveys, stream water samples were collected, together with stream sediments and soil samples, multielementar analytical techniques have been applied with total and/or partial digestion. The results obtained allowed the elaboration of geochemical maps to visualize the distribution of the elements in the territory of Paraná, to establish associations of groups of elements characteristic of the natural environment and the changes imposed by the action of man as well. The multipurpose applications of this geochemical mapping program contribute to geology knowledge, mineral exploration, environmental diagnostics and identification of areas of risk to human health